(untitled) (Research, Society and Development, 2022)
Laboratory errors can occur in any of the three phases of laboratory testing, being preanalytical, analytical or postanalytical. The pre-analytical phase occurs before the examination is performed, being characterized as the phase with the most errors. Preanalytical errors account for 60% to 90% of the interferences that occur in laboratory test results. The collection of information available in the literature on the subject can help to minimize this occurrence. Given the above, the present study aims to present the knowledge discussed in the literature about pre-analytical interferences in laboratory tests. This is a narrative review of the literature. The data sources consulted were SCIELO and Google Scholar, in December 2020. The total number of studies revealed in both data sources was 9,635 studies, of which 28 manuscripts were included. Among the main results found, errors related to the pre-analytical phase of the laboratory stand out, which can directly interfere with the interpretations of professionals who request the exam. In addition, having knowledge of the equipment present in these biochemical sectors is essential for a better conduction of the pre-analytical phase. The dissemination of laboratory quality indicators can encourage the team to visualize actions and investigations with corrective objectives and the prevention of pre-analytical errors. Therefore, the conclusion is that errors in the pre-analytical phase interfere with laboratory results and can cause poor results due to possible misinterpretations. Quality control is essential for the prevention or elimination of pre-analytical errors in laboratory biochemical tests.